Methamphetamine-Induced cardiomyopathy in young adult man: A case report. - Hernandez - Aguirre , U.G,.; Isais - Moreno, D.M.; Prieto-Lavin , C.M.,; Adonia - Machore , M.A. (Revista de Ciencias Médicas Torreón, 2026)
Methamphetamine-associated cardiomyopathy (MACM) causes structural and functional myocardial abnormalities that can progress to advanced heart failure and even necessitate heart transplantation. We present the case of a 23- year-old man with an eight-year history of methamphetamine use and abuse who presented to the emergency department with severe dyspnea on minimal exertion and lower- extremity edema. He denied any personal or family history of cardiovascular disease. Urine toxicology screening was positive for methamphetamines. Physical examination revealed advanced heart failure, classified as New York Heart Association (NYHA) functional class IV. He was hospitalized for three days and treated with diuretics— primarily loop diuretics—showing clinical improvement. Rising methamphetamine use and its initiation at younger ages have contributed to the emergence of MACM in young patients. This underscores the importance of maintaining a high index of clinical suspicion in patients with a history of use, regardless of age. Early cardiological assessment allows for the detection of subclinical ventricular dysfunction and intervention prior to irreversible myocardial damage. We present and discuss the case of a young adult with dyspnea at rest secondary to severe dilated cardiomyopathy associated with chronic methamphetamine use.